2016
DOI: 10.1039/c6py00631k
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of graphene by a TPE-containing polymer using nitrogen-based nucleophiles

Abstract: Through the nitrogen-centered anion reaction of PCT and GO, two new hybrids, RGO-PCT-i and RGO-PCT-s, were successfully prepared and applied as potential optical limiting materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 56 publications
2
19
1
Order By: Relevance
“…It is known that the TPE group adopts a typical configuration owing to the aggregation‐induced emission (AIE) effect: the four propeller‐like phenyl rings undergo an active intramolecular rotation (IMR) process in the solution state to make TPE non‐emissive, whereas in the aggregated state, the restricted IMR process blocks the nonradiative decay channel, which ultimately makes TPE emissive . According to previous reports based on TPE‐containing polymers, if TPE is introduced into a polymer chain, its AIE feature is still effective . In Figure a, P1 exhibits negligible luminescence at λ =497 nm; after the addition of NaH, the emission band is redshifted to λ =561 nm, and this is accompanied by a reddish‐orange luminescence emission under a UV lamp ( λ =365 nm).…”
Section: Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…It is known that the TPE group adopts a typical configuration owing to the aggregation‐induced emission (AIE) effect: the four propeller‐like phenyl rings undergo an active intramolecular rotation (IMR) process in the solution state to make TPE non‐emissive, whereas in the aggregated state, the restricted IMR process blocks the nonradiative decay channel, which ultimately makes TPE emissive . According to previous reports based on TPE‐containing polymers, if TPE is introduced into a polymer chain, its AIE feature is still effective . In Figure a, P1 exhibits negligible luminescence at λ =497 nm; after the addition of NaH, the emission band is redshifted to λ =561 nm, and this is accompanied by a reddish‐orange luminescence emission under a UV lamp ( λ =365 nm).…”
Section: Resultssupporting
confidence: 51%
“…However, there were great differences between them, and the rGO contents of the composites varied from 4.3 to 16.2 %; thus, the degree of functionalization through the same method was different. Among them, the TPE‐containing polymer with large steric hindrance and a rich π‐electron framework was more conducive to improving the solubility of rGO, which was in good accordance with previous reports . So, we wondered whether these differences would still exist for the covalent modification of rGO and whether a stereospecific blockade would still play an important role in improving the solubility of rGO.…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…Since the discovery of the aggregation‐induced emission (AIE) phenomenon by Tang and co‐workers in 2001, AIE materials have attracted a tremendous amount of attention in both condensed‐matter physics and materials chemistry due to their potential applications in, for example, biological probes, chemical sensing, optical waveguides, organic light‐emitting diodes (OLEDs), organic field‐effect transistors (OFETs), liquid crystals, self‐assembly systems, circularly polarized luminescence, and solar cells . However, these AIE materials are usually not suitable for constructing solid nonlinear optical (NLO) devices due to their strong solid‐state aggregation behavior driven by enhanced van der Waals attractive forces between the AIE molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Since the discoveryo ft he aggregation-induced emission (AIE) phenomenonb yT ang and co-workersi n2 001, AIE materials have attracted at remendousa mount of attentioni nb oth condensed-matter physics andm aterials chemistry due to their potentiala pplicationsi n, for example, biological probes, chemical sensing, opticalw aveguides, organicl ight-emittingd iodes (OLEDs), organic field-effect transistors (OFETs), liquid crystals, self-assembly systems, circularly polarized luminescence, and solar cells. [1][2][3][4][5] However,t hese AIE materialsa re usually not suitable for constructing solid nonlinearo ptical (NLO) devices due to their strong solid-statea ggregation behavior driven by enhanced van der Waals attractive forces between the AIE mole-cules.Alarge number of reports have demonstrated that strongi ntermoleculari nteractions can shorten the excitedstate lifetime, add relaxation pathways, and thereby reduce ef-fectiveN LO absorption. [6][7][8] To address this problem,i tw ould be highly desirable to designa nd synthesize non-aggregation functional materials with AIE moieties for NLO and opticall imiting (OL) devicesb ya xially graftingA IE molecules or polymers onto fused 2D nanosheets (e.g.,g raphene, [9] graphene oxide (GO), [10] reduced graphene oxide (RGO), [11] transition-metal dichalcogenides (MX 2 ,X = S, Se;M = Mo, Nb, W, Ta), and fewlayer black phosphorus (BP)).…”
Section: Introductionmentioning
confidence: 99%